Land use efficiency and influencing factors of urban agglomerations in China. (November 2019) - Yu, Junqing; Zhou, Kaile; Yang, Shanlin
Highlights: Eco-efficiency of China's 12 urban agglomerations are evaluated. Economic radiation capabilities of the UAs' core cities are investigated. Some highly developed UAs in China did not achieved high eco-efficiency. Some suggestions for sustainable development of China's UAs are proposed Abstract: The rapid urbanization in China has a huge impact on land use. The scarcity of land resources has become a constraint for sustainable urban development. Recently, urban agglomeration (UA) has become a new type of complex urban system. The aim of this paper is to investigate the relationship of land use and UAs' socio-economic development, and figure out effective land strategies. There are 12 evaluated UAs in our paper, which includes 184 cities. We analyze the land use performance of China's UAs from different perspectives. We first analyze the decoupling relationship between economic growth and urban land use, and then evaluate land use efficiency of China's 12 typical UAs. The k-means clustering is used to clarify evaluated UAs into different groups according to their characteristics. Furthermore, the efficiency decomposition, changing trend and comparison of core cities are also described. At last, the tobit regression model is built to verify the main driving factors of land use efficiency from three aspects, including economic level, economic structure and government regulation. The results show that most UAs showed weak decoupling relationship. Average urban land use efficiency of UAs in China was not very high. Furthermore, the average efficiency showed an evident fluctuation in 2008 and 2015. Yangtze River Delta and Pearl River Delta have been on the effective frontier. Based on group analysis, the UAs in central China have more room for efficiency improvement. The significant factors influencing UAs' land use efficiency included per capita GDP, population density and the degree of market openness. Finally, several targeted strategies are proposed to improve urban land use performance of China's UAs.